BIOM-14. METHODS FOR SCREENING AND MONITORING BY GBM MASTER REGULATORY GENE MARKERS IN LIQUID BIOPSY. (9th November 2020) - Liu, Tianyi; Le, Son; Tran, David
Abstract: BACKGROUND: Current liquid-based cancer screening relies on massive deep NGS to detect rare cancer cell-derived genetic materials - a costly method fraught with high false-negative and false-positive rates. We aim to develop a non-NGS-centered, AI-directed liquid-based detection of GBM stem-like cells (GSC). METHODS: Utilized a robust AI suite, NETZEN, we defined a common master regulatory gene network (MRGN) in GSC. Since master regulators (MR) in MRGN are developmentally restricted, their chromosomal loci are accessible in GSC but not in normal cells. Downstream factors in MRGN are massively overexpressed in GSC compared to normal cells. Thus, we measured 1) accessibility of MR genes using transposase/transposons carrying unique barcodes that can be detected after insertion into the MR's predetermined accessible locations, and 2) expression of downstream factors using nested qRT-PCR, in PBMC from healthy controls spiked with known quantities of GSC or patients with GBM. RESULTS: We characterized 10 MR genes in GSC with ≥1 GC-rich promoter region that is hypomethylated and accessible (ATACseq) in GBM/GSC per GSE70175/92460/52271 (19 samples) and GSE67633/96088 (14 samples), and hypermethylated and inaccessible in lymphocytes/PBMC per GSE98837 (6) and GSE74912 (13), respectively. Using barcoded transposons, we specifically disrupted 4 MR's accessible regions only in GSC, not in PBMC. We also characterized 50 upregulated downstream factors with the top 20 having 3 to 5-orders-of-magnitude higher mean expression in GSC compared to PBMC (GSE79362/86884, 451 samples). Currently our method has a detection limit of 0.2–1 GSC in 10 6 PBMC. Using the first iteration, we detected GSC's MRGN in blood samples of 14/14 GBM patients before resection, compared to in none of 15 healthy donors. CONCLUSIONS: Chromosomal accessibility of MR and signal amplification in MRGN of GSC provide powerful substrates for a non-NGS, low-cost, liquid-based GBM detection system with potentially high sensitivity and specificity. Further testing and optimization are ongoing.